Potential role of polyphenolic standardized chokeberry extract (Aronia melanocarpa) on COVID-19 infection caused by SARS COV-2 virus and its cardiometabolic complications - Mitrović, Miroslav; Tasić, Nebojša; Jakovljević, Vladimir Lj.; Tasić, Danijela; Mitrović, Nikola M. (PONS - medicinski časopis, 2021)
The COVID-19 pandemic marks the time in which we live. More than 167 million people have been infected so far, and over 3 million people have died. Cardiometabolic risk factors increase during COVID-19 is large due to isolation and sedative lifestyle, higher food intake. Serbia belongs to the group of countries with a high cardiovascular risk. The meta-analysis confirmed the relationship between the severity of cardiometabolic diseases and the development of a more severe clinical sings of COVID-19, while the metabolic syndrome is a significant inducer of disease complications. Endothelial dysfunction in patients with metabolic syndrome plays an important role in the development of COVID-19 complications. Any activity that leads to a reduction in inflammatory processes in the endothelium and improvement of microcirculatory function is beneficial. Polyphenolic compounds have potential to show a beneficial effect during prevention and treatment of COVID-19. Aronia melenocarpa polyphenol extract is a product that promises. Strong anti-inflammatory action, as well as a high degree of bacteriostatic and antiviral activity, including activity against the SARS-CoV-2 virus has been proven by clinical trials. Aronia extract in in vitro experiments leads to direct inactivation of various viral cultures: influenza A (99.99%), SARS-CoV-2 virus (96.98%) and adenoviruses (93.23%). With its systemic action, aronia extract manages to significantly affect the symptoms and parameters of the metabolic syndrome, so as such it is a logical and efficacy food supplement choice in the prevention and treatment of COVID-19 including and post-COVID-19 symptoms.